2012
DOI: 10.1089/cell.2011.0066
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Bone Marrow Cells Do Not Provide New Oocytes But Rescue Fertility in Female Mice Following Treatment With Chemotherapeutic Agents

Abstract: It is generally accepted that mammalian females are born with a finite pool of oocytes and that this is the sole source of ovules throughout the reproductive life of the adult. This dogma was shaken in 2003 when researchers showed that the oocyte stock might be renewable in adult mammals. It has been proposed that hematopoietic stem cells might be a source of new oocytes. These discoveries have puzzled many researchers and remain controversial. In our study, we attempted to determine if transplanted bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
(31 reference statements)
1
24
0
Order By: Relevance
“…In recent years, interest has rapidly grown in studies exploring the therapeutic potential of stem cells because of their potential to differentiate into various specialized cell types. This characteristic has been observed in stem cells derived from a number of different sources, including bone marrow [68], amniotic fluid [9], and adipose tissue [10, 11], and all of these cell types have been shown to have therapeutic effects on long-term infertility and ovarian damage. However, many of the suitable cell types currently identified for human use are either difficult to obtain or obtaining them involves invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, interest has rapidly grown in studies exploring the therapeutic potential of stem cells because of their potential to differentiate into various specialized cell types. This characteristic has been observed in stem cells derived from a number of different sources, including bone marrow [68], amniotic fluid [9], and adipose tissue [10, 11], and all of these cell types have been shown to have therapeutic effects on long-term infertility and ovarian damage. However, many of the suitable cell types currently identified for human use are either difficult to obtain or obtaining them involves invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…They did not detect germ cell transmission from the donor. Santiquet et al (2012) transplanted BM cells in PU.1 mice and in SCID mice after treatment with chemotherapeutic agents. They found no evidence that transplanted BM cells provide new fertilizable oocytes in PU.1 mice or SCID mice.…”
Section: The Development Of Germ Cells In Postnatal Mammalian Ovariesmentioning
confidence: 99%
“…These cells triggered the expression of the FSH receptor gene, synthesis of FSH receptors, oestrogen hormone production, and folliculogenesis in ovaries of FORKO mice (Ghadami et al, 2012). However, Santiquet et al (2012) reported that there was no evidence that BMT or bovine embryonic ovarian tissue grafts led to the production of new oocytes in PU.1 and SCDI mice following treatment by chemotherapeutic agents. Nevertheless, the influence of BM cells improved the fertility of SCID mice that had been previously exposed to chemotherapeutic agents (Santiquet et al, 2012).…”
Section: The Extra-gonadal Source Of Female Germline Stem Cells Aftermentioning
confidence: 99%
“…However, Santiquet et al (2012) reported that there was no evidence that BMT or bovine embryonic ovarian tissue grafts led to the production of new oocytes in PU.1 and SCDI mice following treatment by chemotherapeutic agents. Nevertheless, the influence of BM cells improved the fertility of SCID mice that had been previously exposed to chemotherapeutic agents (Santiquet et al, 2012). Thus, Santiquet et al (2012) have suggested that the positive effects of transplanted bone marrow (BM) cells on the fertility of female mice could be due to renewal of self-tolerance of ovarian antigens; thereby, follicles are not demolished by chemotherapeutic agent treatment as a result of autoimmune damage.…”
Section: The Extra-gonadal Source Of Female Germline Stem Cells Aftermentioning
confidence: 99%
See 1 more Smart Citation